Short-term follow-up of patients after aneurysmectomy of the left ventricle - Silveira,Wilson Luiz da (2000)
OBJECTIVE: Left ventricular aneurysm is a complication of myocardial infarction that can best be treated by reconstructive surgeries that can restore ventricular geometry. We analyzed immediate results in a group of consecutive patients who underwent surgical correction of left ventricular aneurysms. METHODS: From January '90 to August '99, 94 patients - mean age 58.4 (ranging from 36 to 73 years), 65 (69.1%) males and 9 ( 30.8%) females - were operated upon. Pre-operative ejection fraction ranged from 0.22 to 0.58 (mean = 0.52), and the aneurysm was located in the antero-lateral area in 90.4% of the cases. Functional class III and IV (NYHA) was present in 82 (87.2%) patients, and 12 (12.7%) were in functional class I and II. Congestive heart failure was the most frequent cause (77.6%), occurring in isolation in 24.4% or associated with coronary artery diseases in 53.2%. RESULTS: Short-term follow-up showed a 7.4% mortality, and low cardiac output was the main cause of death. Coming off pump was uneventful in 73 patients (77.6%), with a 3.2% mortality and with the use of inotropics in 20 (21.3%). One patient (1%) did not come off the pump. CONCLUSION: Surgical correction was adequate in the immediate follow-up of operated patients, and mortality was higher in patients with higher functional class.